COVID-19-RELATED VACCINES AND THERAPEUTICS;PRELIMINARY INSIGHTS ON RELATED PATENTING ACTIVITY DURING THE PANDEMIC (WORLD INTELLECTUAL PROPER, 2022)
Since the start of the COVID-19 pandemic there have been remarkable research and innovation efforts to fight the SARS-COV-2 virus and the related disease. This patent landscape report provides early observations on the patenting activity which took place in the field of COVID-19 vaccines and therapeutics, and compares results with clinical trial data for related candidate vaccines and drugs
Keywords: COVID-19 (Disease); Patents.; Patents (International law); COVID-19; COVID-19.; Brevets d'invention (Droit international); Patents